AKSES UMKM TERHADAP PEMBIAYAAN MIKRO - ris yuwono yudo nugroho; Rinda Safitriatul Jannah (Cakrawala Management Business Journal, 2020)
This study proposes to determine the access of MSMEs to financial services at financial institutions. Furthermore, it aims to see the factors that affect MSME players' access to financing services at sharia BMT financial institutions. This research method uses a non-probability (non-random) sampling technique with purposive sampling, including 60 respondents, 30 respondents who become BMT customers, and 30 respondents become BMT non-customers. The results of the probit model regression test in this study show that three variables affect for access of MSME to microcredit, including age (x1), house distance (X4), and business location (X5). Meanwhile, variables that do not affect access of MSME to Islamic micro-credit financing are Initial Capital (X2), and Assets (X4).